2007
DOI: 10.1111/j.1540-8159.2007.00570.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Pulmonary Vein Isolation on the Morphology of P Waves: The Contribution of Pulmonary Vein Muscle Excitation to the Formation of P Waves

Abstract: The excitation of cardiac muscle tissue, which has migrated to the pulmonary veins, was thus found to play an important role in the formation of the middle part of the P wave/loop.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…This would correlate with the different findings of Ogawa et al and Date et al wherein they found reduction and no change, respectively, in the width of the P wave after CPVI during long-term follow-up. 7,8 The decrease in the LA activation time due to earlier propagation of the medial wave front seen in 24% of our patients would explain the reduction in the width of the P wave as observed by Ogawa et al 7 …”
Section: La Activation Pattern and Timingsmentioning
confidence: 57%
See 2 more Smart Citations
“…This would correlate with the different findings of Ogawa et al and Date et al wherein they found reduction and no change, respectively, in the width of the P wave after CPVI during long-term follow-up. 7,8 The decrease in the LA activation time due to earlier propagation of the medial wave front seen in 24% of our patients would explain the reduction in the width of the P wave as observed by Ogawa et al 7 …”
Section: La Activation Pattern and Timingsmentioning
confidence: 57%
“…Numerous studies have demonstrated some varying effects of PV isolation (PVI) on the P-wave duration in the electrocardiogram (ECG), atrial size, LA function and activation. [7][8][9][10] Successful PVI was reported to significantly reduce the LA size on long-term follow-up. 9 Increased LA activation times are observed in patients who underwent repeat procedure after PVI.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The VCG may also be applied to the study of atrial loops. Date et al [22] could identify the role of the cardiac tissue surrounding the pulmonary veins in the formation of the P wave and thus the changes that pulmonary vein isolation …”
Section: The Vectorcardiogrammentioning
confidence: 99%
“…However, the standard ECG does not provide spatial information that can be obtained with a vectorcardiogram (VCG). The VCG allows the observation of the contribution of a specific tissue region on the morphology of P waves after isolation of the pulmonary veins [22] and spatial parameters derived from the VCG constitute a risk factor in post myocardial infarction patients [4]. Also, the study of the VCG during AF allows the extraction of spatial characteristics of AF waves that have been related to the organization of the atrial activity during AF [102].…”
Section: Introductionmentioning
confidence: 99%